2015
DOI: 10.3126/njog.v10i1.13189
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Surgical Abortion in the Second Trimester of Pregnancy

Abstract: Aims:This study was done to know the demographic profile of women undergoing second trimester abortion at Kathmandu Model Hospital. The aim was to see the success rate of combination of mifeprostone and misoprostol for the medical induction and misoprostol alone for the cervical dilation in case of surgical evacuation. Methods:A retrospective study was done by looking at the profiles of 540 clients on whom second trimester abortion was performed during the period of October 2010 to October 2014. Twenty-nine wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
7
3
1
Order By: Relevance
“…In this study most of the clients underwent medical induction followed by dilatation and evacuation (56.25%) that is similar to the reports of Karki et al 10 and Chhetri et al 15 However these studies have not mentioned about the complications occurred during the procedure but we observed that few cases had retained POC and excessive bleeding leading to blood transfusion.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study most of the clients underwent medical induction followed by dilatation and evacuation (56.25%) that is similar to the reports of Karki et al 10 and Chhetri et al 15 However these studies have not mentioned about the complications occurred during the procedure but we observed that few cases had retained POC and excessive bleeding leading to blood transfusion.…”
Section: Discussionsupporting
confidence: 88%
“…Provincial hospital Jananakpurdham is situated in Dhanusa district so most patient belonged to this district. Most of the clients were under 30 years of age, poor literacy rate and multiparous which are similar to the findings of Karkiet al 10 and Shrivastva et al 11 In this study maternal mental health was major indication for second trimester abortion which was similar to that of Karkiet al 10 but contrary to that of Anderson N et al 12 , Boyd PA et al 13 and Shaffer BL et al 14 where majority had some anatomic or genetic anomalies of fetus. Similarly Shrivastvaet al 11 also had different result where unwanted pregnancy due to various reasons was major indication.…”
Section: Discussionsupporting
confidence: 86%
“…Out of 36 clients in the second trimester, most of the clients were at early gestational age 13-15 weeks (52.77%). Majority of them, 88.88% had MI and very few, 11.11% had D & E which is in consistent with findings from study at Kathmandu Model Hospital which showed most of the clients were in 12-14 weeks (52.40%) and 94% of clients had MI and 5.37% had D&E. 10 The main reason for seeking CAC service in first trimester in our study was completed family (39.25%) and short spacing/ postpone child bearing (29.62%). The findings of our study is comparable to that of study at TUTH which showed the reason for seeking CAC was completed family (55%) followed by unwanted pregnancy (33%) 8 whereas a retrospective study in CAC and PAC center of a maternity hospital in Nepal showed that the major reason for seeking abortion was too many children (59%) followed by illegitimate pregnancy (16%).…”
Section: Discussionsupporting
confidence: 88%
“…Among the total CAC clients, the vast majority of clients 83.62% (n=143) refused to take any methods of post abortion contraception whereas only 16.37% (n=28) of clients accepted contraception which is comparable to other study. 10 This is in contrast to previous studies 11,8,14 where contraceptive acceptance was quite high which could be either due to effective counselling by trained counsellor or setting precondition for abortion service (compulsory acceptance of a contraceptive method upon receiving CAC service). 15 The most common accepted method was implant, followed by DMPA in our study.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation